Exploring a Forced Migration Movement in the Period of the Cold War from the (Former) U.S.S.R. to Abroad - Oksana Koshulko (Budapest International Research and Critics University, 2023)
The paper studied extremely important categories in the (former) U.S.S.R. such as dissidents, forced (exiled) emigrants, refugees, asylum seekers, and ‘non-returnees’ to their country of origin because of the political persecution in the 20th century, as well as, in the 21st century the category of ‘Foreign Agents’ in contemporary Russia in the period of Russia’s full invasion of Ukraine for the political persecution too, when this successor country of the U.S.S.R. found enemies and agents again among its citizens, who tell the truth about Russia’s war 2014-2022- in Ukraine. All the categories of ‘enemies’ and ‘agents’ of the 20-21st century have been characterized and analyzed in the paper. Also, the movement of refugees and asylum seekers from 1975 to 1990, from the U.S.S.R. to the U.S.A. has been summarized and analyzed in the paper.